A double perovskite BiLaCoMnO6: synthesis, microstructural, dielectric and optical properties. (3rd April 2023) - Parida, S. K.; Satapathy, Tanushree; Mishra, S.; Choudhary, R. N. P.
ABSTRACT: In this paper, synthesis (solid-state reaction) and characterization (XRD, SEM, EDX, RAMAN, UV & LCR) of a double perovskite: BiLaCoMnO6 (BLCMO) are reported. The structural analysis suggests monoclinic crystal symmetry with average crystallite size = 79.6 nm and lattice strain = 0.00149 respectively. The analysis of the scanning electron microscopy (SEM) micrograph suggests the uniform distribution of grains. The analysis of energy-dispersive X-ray spectroscopy (EDX) spectrum suggests the presence of all constituent elements (Bi, La, Co, Mn & O) in both weight and atomic percentage. The study of the Raman spectrum provides information about the atomic vibration of all the constituent elements. The study of the UV visible spectrum provides of bandgap energy of 2.06 eV and impedance spectroscopy suggests a negative temperature coefficient of resistance (NTCR) character, while the modulus study predicts the presence of a non-Debye type of relaxation. The study of temperature-dependent resistance supports NTC thermistor applications.